2020
DOI: 10.1162/jocn_a_01468
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Your Mind's Eye during Recollection: Decoding the Long-Term Recall of Short Audiovisual Clips

Abstract: Unlike familiarity, recollection involves the ability to reconstruct mentally previous events that results in a strong sense of reliving. According to the reinstatement hypothesis, this specific feature emerges from the reactivation of cortical patterns involved during information exposure. Over time, the retrieval of specific details becomes more difficult, and memories become increasingly supported by familiarity judgments. The multiple trace theory (MTT) explains the gradual loss of episodic details by a tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 86 publications
(91 reference statements)
0
4
0
Order By: Relevance
“…Second, the present study raises the question of how the different kinds of consolidation mechanisms (synaptic vs systemic), as well as how the different memory/processing systems interact during the encoding and the consolidation of visual memories 46 , 47 . General theories of memory (e.g.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Second, the present study raises the question of how the different kinds of consolidation mechanisms (synaptic vs systemic), as well as how the different memory/processing systems interact during the encoding and the consolidation of visual memories 46 , 47 . General theories of memory (e.g.…”
Section: Discussionmentioning
confidence: 94%
“…Memory phenomena result in large part from both external, slow, pervasive, and cortex-based mechanisms of learning, and on transitory associative representations formed and maintained within the medial temporal lobe memory system 46 , 53 55 . In addition, important changes in the functional connectivity between the hippocampus and cortical areas operate during memory consolidation, especially with a progressive disengagement of the Medial Temporal Lobe and both synaptic and systemic consolidation in the neocortex 47 , 56 , 57 . How those different memory systems interact and how a redescription of knowledge operates over time and consolidation remain a challenge for further research.…”
Section: Discussionmentioning
confidence: 99%
“…In an EEG study, Larzabal et al (2020) also used video clips but tested participants' remember/know judgements of frames from those clips at delays of hours, one day and three weeks. Using MVPA of the EEG signal to classify new and old items, they, too, found sustained patterns indicative of reinstatement effects that correlated with recollection.…”
Section: Multivariate Analyses and Memory Representations In System Consolidationmentioning
confidence: 99%
“…Specifically, are the prestimulus neurons that were activated, or subset of them, also re-activated post-encoding, and does the latter set also support representations of detailed, remote memories? There is no definitive answer, but Larzabal et al's (2020) study tracking memory to reinstatement effects suggests that it is possible that similar neural populations are implicated at all time points. Using MVPA of the EEG signal to video clips, they found that although the signal faded over time, sustained patterns indicative of reinstatement effects were…”
Section: Mpfc and Hippocampus In Formation Of Episodic Memories: Pre-stimulus And Postencoding Effects On Consolidationmentioning
confidence: 99%